2017
DOI: 10.1590/0103-8478cr20160908
|View full text |Cite
|
Sign up to set email alerts
|

Plant extract and essential oils added as antimicrobials to cheeses: a review

Abstract: Cheese is a food that is highly susceptible to contamination by pathogenic and spoilage microorganisms, which can result in a decrease in its shelf life and cause serious risks to the consumers’ health. Consumers always require healthy food, free of synthetic preservatives, inducing a search for natural alternatives to ensure safety of the products. Essential oils and plant extracts emerge as an alternative for aiding cheese preservation. Some substances have demonstrated good effects against most pathogens an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 34 publications
0
44
0
5
Order By: Relevance
“…According to Moro et al (2015), the strong specific flavor of thyme oil, although used in small concentrations, can significantly affect sensory quality of dairy products and may result in their rejection. Gouvea et al (2017) stated that acceptance of food products based on essential oils or plant extracts is extremely important, because having high antimicrobial effect is not enough if consumer doesn't approve it in a sensory way. Divergent results have been reported in several studies, including those of Leuschner and Ielsch (2003), Hayaloglu and Fox (2008), Gammariello et al (2008), who all affirmed that TEO has been successfully incorporated into cheese and have been well accepted by consumers.…”
Section: Evaluation Of Sensory Cheese Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Moro et al (2015), the strong specific flavor of thyme oil, although used in small concentrations, can significantly affect sensory quality of dairy products and may result in their rejection. Gouvea et al (2017) stated that acceptance of food products based on essential oils or plant extracts is extremely important, because having high antimicrobial effect is not enough if consumer doesn't approve it in a sensory way. Divergent results have been reported in several studies, including those of Leuschner and Ielsch (2003), Hayaloglu and Fox (2008), Gammariello et al (2008), who all affirmed that TEO has been successfully incorporated into cheese and have been well accepted by consumers.…”
Section: Evaluation Of Sensory Cheese Qualitymentioning
confidence: 99%
“…Tayel et al (2015) also confirmed that addition of TEO to cheeses resulted in good sensory acceptance. Gouvea et al (2017) mentioned that general acceptance of cheeses with essential oils and plant extracts can be facilitated if consumers are already familiar with this type of products. To overcome taste problems, Gutierrez et al (2008) proposed combination of different essential oils and extracts to have good antimicrobial effect without affecting product taste and smell.…”
Section: Evaluation Of Sensory Cheese Qualitymentioning
confidence: 99%
“…If most hard or semi-hard raw milk cheeses are usually ripened long enough to be safe for consumption, traditional soft cheeses continue to be a real hazard for public safety, as they provide appropriate environment for pathogens survival and development (10,11). A continuous search of antimicrobial solutions, adequate as natural additives in foods in general and in cheeses, in particular, has increasingly been reported by recent studies (12)(13)(14)(15)(16)(17). Enrichment of cheeses with Nigella sativa seed oil (NSSO) has been studied by several authors, mostly for its antimicrobial properties (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Goat milk differs from cow and human milk in having better digestibility, buffer capacity, alkalinity, and therapeutic values, as well as having fat with better physical properties (i.e., surface tension, viscosity, and specific gravity) than cow milk (Park et al, 2007). Goat milk is commonly used for the production of fresh unripened cheese (Janštová et al, 2010), a versatile nutrient-dense dairy product susceptible to physical, chemical, microbiological, and biochemical spoilage that can decrease its shelf life and cause serious risks to consumers' health (Jalilzadeh et al, 2015;Gouvea et al, 2017;Khorshidian et al, 2017). Changes that limit shelf life include creaming of fat, gelation of protein solutions, syneresis of curds and crystallization of minerals, nonenzymatic browning and oxidation of fat, growth of microorganisms, enzymatic degradation, ripening of cheese, and fermentation (Kilcast and Subramaniam, 2011).…”
Section: Introductionmentioning
confidence: 99%